LAYANAN BIMBINGAN KELOMPOK MENGGUNAKAN TEKNIK PROBLEM SOLVING UNTUK MENINGKATKAN KECERDASAN EMOSIONAL SISWA KELAS XI MAN 01 BANDUNG BARAT - Naila Mahabbah; M. Afrilianto; Tiara Agustine (FOKUS : Kajian Bimbingan dan Konseling dalam Pendidikan, 2026)
The focus of this research is to improve the emotional intelligence of students in class XI MAN 01 West Bandung through group guidance services using problem solving techniques. This research applies a mixed method with Explanatory Sequential Design. Based on data collection with a one group pretest posttest design model. The data obtained were normally distributed, so the analysis was carried out using parametric statistics through the paired sample t-test. The test results show a significance value of 0.000, and the hypothesis is accepted because the significance value is less than 0.05. Therefore, the findings in this study imply that group guidance services using problem solving techniques can effectively improve the emotional intelligence of students in class XI MAN 01 West Bandung.